O conhecimento sobre a sistematização da assistência de enfermagem entre os anos de 1980 e 2005 : subsídios para a qualidade do cuidado - Venturini, Daniele Aparecida (2007)
Nursing Care Systematization - NCS - consists of a method whose main purposes are to organize the care process and to provide individualized quality service. The present study consists of a bibliographical research, whose objective was to analyze Brazilian publications regarding the Methodology of Nursing Care. The collection of data began in September 2006 and was concluded in July 2007. The analysis method used was content analysis, as proposed by Bardin (2004). The sample was comprised of 37 papers: 34 articles, two master's dissertations and one doctorate thesis, published between 1980 and 2005. The search for these works was carried out in the following databases: Bireme, Capes Thesis Database and Virtual Health Library. The keywords used, besides NCS, were Methodology of Nursing Care and Nursing Process, care, care planning, quality of nursing care, records and nursing annotations. Data treatment began with the pre-selection of the material, through the reading of the titles and abstracts. Next, the selected studies were filed for later retrieval. Each work was subjected to an analysis guideline. After several readings and explorations of the material, the works were codified and thematic categories were extracted from them, as well as examples of each. Four thematic categories were obtained from the analyzed texts: related to teaching, to the institution, to the professionals, and to the administration. Each category was composed of subcategories. The category related to teaching had three subcategories (formation and training of professionals; the role of teaching institutions and research output; and the continuation of learning through certifications and training). The hospital institution category had two subcategories (personnel policy; and institutional policy and physical, human, material and financial resources). In the category related to professionals, the study identified outcomes resultant of intrinsic and extrinsic factors, as well as from the advantages incorporated by NCS to the profession. As for the administration category, three subcategories were highlighted: human resources administration; the administrative process; and nursing care administration. Among the main difficulties for the implementation of NCS, extracted from the analyzed studies, are those related to the training of professionals, lack of support from management, and personal resistance and beliefs by professionals. The benefits provided by NCS relate both to professionals as well as to patients and the institution alike. In spite of considering NCS a challenge for the third millennium, the difficulties and benefits for its implementation should be investigated and publicized, so that the practice is rethought, and the actions of nurses find support for these changes.